Design and fabrication of coconut shell charcoal crusher machine for briquette production - Azwinur Azwinur; Andi Gilang Wira Pratama Azwinur; Zaini (Journal of Mechanical Engineering and Fabrication, 2026)
Charcoal briquettes are an alternative fuel with a high carbon content, high calorific value, and a longer burning time than conventional fuels. Coconut shells are one potential raw material, but the crushing process is still often done manually, making them less efficient. This research aims to design and build a coconut shell charcoal crusher to improve process efficiency and add value to biomass waste. The research method includes the design, fabrication, and testing stages of the device. The manufacturing process includes frame design, material cutting, welding, assembly, and finishing. Tests were conducted with varying charcoal masses to determine the device's performance based on grinding results and processing time. The test results showed that the device is capable of producing two levels of fineness: fine and coarse. A 1 kg charcoal sample yielded 200 grams of fine and 800 grams of coarse charcoal in 1 minute and 50 seconds. A 3 kg charcoal sample yielded 600 grams of fine and 2400 grams of coarse charcoal in 3 minutes and 50 seconds, while a 5 kg sample yielded 1100 grams of fine and 3900 grams of coarse charcoal in 7 minutes and 30 seconds. These results indicate that increasing the amount of material is directly proportional to the processing time and production yield. The fine fraction is more suitable for briquette molding, while the coarse fraction requires further processing. Thus, the designed tool can increase the efficiency of the crushing process and support the utilization of coconut shell waste as an alternative energy source